Effect of unconventional waters irrigation on some morphological and physiological parameters of barley - Fellah, Sihem; Ababsa, Nawal; Atmani-Merabet, Ghania; Sadouki, Asma (Journal of Agriculture and Applied Biology, 2024)
A test on a variety of barley “Fouara” was carried out to verify the effects of treated wastewater on some physio-morphological parameters of this plant. Two different types of irrigation were chosen, one using treated wastewater from the Ain Beida wastewater treatment plant, and the other, ordinary water serving as a control. The physicochemical results of the treated wastewater showed, in particular, the EC, NH4, NO3 and the DCO/DB05 ratio do not exceed the admissible standards when they reach their maximum values The physio-morphological parameters of barley respond positively to the use of this water; represented by the two averages of the 'sugar' parameter which shows a clear difference depending on the water category (T and S) or the control individuals express an average (0.055) significantly lower than that of the S individuals (0.847). We note that significant values of the positive correlation coefficient of r=0.812 between the two parameters TRE and SF, therefore there is an association between these two factors. But negative for the TRE and PSF (r = -0.722). This means that the values of the two parameters do not evolve in the same direction. The factors 'sugar' and 'chlorophyll b' present the best correlation, they better represent the six individuals and the proline contents are higher in the treated plants.